Dinamika Koordinasi Antar-Lembaga dalam Implementasi Program Nasional Tiga juta Rumah studi di Buton Selatan - Andi Tenri Andi; La Didi; La Ode Muhamad Hamid (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study analyzes the dynamics of inter-agency coordination in the implementation of the National Three Million Houses Program in South Buton, which is crucial for providing adequate housing. Although this program represents a commitment of the central government, its effectiveness at the regional level largely depends on coordination among institutions, which is often hindered by geographical and administrative challenges in archipelagic areas. This study employs a qualitative approach with a case study design, collecting data through in-depth interviews, observation, and documentation. The main findings reveal two fundamental constraints: the lack of consistent policy information dissemination and delays in inter-organizational responses. Inconsistent information leads to ambiguity in interpretation and operational differences, while delayed responses create a domino effect that hampers program progress and postpones the fulfillment of housing needs. To address these issues, this research proposes an inter-agency collaboration model based on integrated collaborative governance that emphasizes actor interdependence, active stakeholder participation, and regulatory alignment, in line with the theories of Collaborative Governance and Network Governance. This model aims to minimize variability in bureaucratic commitment and the complexity of administrative procedures in order to accelerate the realization of the program. The implications of this research highlight the importance of shifting toward a collaborative and partnership-based approach to enhance the effectiveness of national housing programs.